Clinical features of benign epilepsy of childhood with centrotemporal spikes in chinese children. Issue 4 (January 2017) - Liu, Meng-Jia; Su, Xiao-jun; MD, Xiu-Yu Shi; Wu, Ge-fei; Zhang, Yu-qin; Gao, Li; Wang, Wei; Liao, Jian-xiang; Wang, Hua; Mai, Jian-ning; Gao, Jing-yun; Shu, Xiao-mei; et al.
Abstract : Abstract: This multicenter clinical trial was conducted to examine current practice of benign epilepsy with centrotemporal spikes and especially address the question that in what circumstances 1 antiepileptic drug (AED) should be preferred. Twenty-five medical centers participate in this clinical trial. The general information, clinical information, and treatment status were collected under the guidance of clinicians and then analyzed. Difference between different treatment groups was compared, and usefulness of the most commonly used AEDs was evaluated. A total of 1817 subjects were collected. The average age of the subject was 8.81 years. The average age of onset is 6.85 years (1–14 years). Male-to-female ratio is 1.13:1. A total of 62.9% of the patients are receiving monotherapies, and 10.6% are receiving multidrug therapy. Both age and course of disease of treated rolandic epilepsy (RE) patients are significantly different from those of untreated patients. Bilateral findings on electroencephalography (EEG) are less seen in patients with monotherapy compared with patients with multidrug therapy. Except for 25.4% patients not taking any AEDs, oxcarbazepine (OXC), sodium valproate (VPA), and levetiracetam (LEV) are the most commonly used 3 AEDs. VPA and LEV are commonly used in add-on therapy. OXC and LEV are more effective as monotherapy than VPA. Age of onset of Chinese RE patients is 6.85 years. Bilateral findings on EEG could be a risk factor to require multidrug therapy. In Chinese patients, OXC, VPA, and LEV are most commonly used AEDs as monotherapy and OXC and LEV are more effective than VPA.